RETRACTED: DEFINING AND FRAMING ISLAMIC ECONOMICS AS ISLAMIC MORAL ECONOMY: AN ATTEMPT TO EMBED PUBLIC POLICY IN ISLAMIC ECONOMICS TO GENERATE EMERGENCE SCIENCE - Mehmet Asutay (Share: Jurnal Ekonomi dan Keuangan Islam, 2016)
This manuscript HAS BEEN RETRACTED on the request of the author. Therefore, a reasonable effort should be made to remove all references that links to this article.